A Socio-economic Study on Pros & Cons of SRI Method of Paddy Cultivation In Ormanjhi Block of Ranchi District, Jharkhand - Agarwal, Punit Kumar; Kumar, Ajay (Indian Journal of Extension Education, 2017)
Rice is a staple food for more than half of the world’s population. A major issue with the traditional system of paddy production, particularly green revolution technology is input intensive and favors cash rich farmers. Increasing prices of agricultural inputs prevent poor farmers from completely adopting modern production technologies. Under such circumstances the System of Rice Intensification (SRI) method was suitable and followed by the farmers. System of rice intensification is a method for increasing the productivity of rice cultivation while at the same time reducing inputs, including seeds and fertilizers, and water requirements. The present study was conducted in Hindebli, Kuchu, Tapa, Khulsi and Bundu villages of Ormanjhi block of Ranchi district. In this study the main objectives were to study the socio-economic profile of paddy growers, perception and constraints confronted by paddy growers under SRI method of paddy cultivation. Study revealed that the major constraints in SRI production were lack of awareness, Scarcity of skilled labour, nursery management, and drudgery in cono-weeder uses. The major perception regarding SRI method of paddy cultivation were low demand of water, higher production or yield, remuneration from government, low seed requirement, low costs of input uses.
Keywords: SRI Method of Paddy Cultivation; Constraint in SRI Method; Reasons for Adoption of SRI Method